KONSTRUKSI FILSAFAT ISLAM TERHADAP FILSAFAT YUNANI DAN FILSAFAT BARAT MODERN - Jauhari, Sofuan (Ngabari: Jurnal Studi Islam dan Sosial, 2020)
In the academic world, there is often debate about the influence of Greek philosophy, Islamic philosophy, and modern Western philosophy on each other. Does Islamic philosophy was influenced by Greek philosophy or vice versa? And does modern Western philosophy influenced by Islamic philosophy or vice versa? This paper aims to discuss the contribution of Islamic philosophy to the existence of Greek philosophy and modern Western philosophy. Through the literature review method, this paper finally resulted in the finding that both Greek philosophers, Muslim philosophers, and Modern Western philosophers had both been teachers and students for each other.